Seasonal anthropometric changes using 3-dimensional whole body scanner in collegiate female swimmers - Kawada, S.; Hakamada, N.; Funato, K. (2007)
Competitive seasons of swimming are generally divided into almost 2 stages in a year. For instance, the first half period is to the first main meets on April since last October, and then the second half period is to the main meets on September since May. Over the past years, several studies have been made on body composition by anthropometric measurements [1]. But there has been no study that tried to measured this three-dimensional anthropometry method in athletes. This investigation was to monitor the body shape longitudinally by using three-dimensional anthropometry method (BLS: Body line scanner, Hamamatsu Photonics KK) in female collegiate swimmers, as the subjects in first half period (during the 5 months: since May). June is basic fraise; endurance training (B) and August is taper fraise; conditionings (T). Furthermore, these separate body composition parameter of August compared with June.